2022
DOI: 10.3390/cancers14071699
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hypolipidemic Drugs and the Risk of Second Primary Malignancy in Colorectal Cancer Patients

Abstract: An increasing number of studies has brought evidence of the protective role of statin use against different types of cancer. However, data on their association with second primary malignancies (SPMs) are lacking. The purpose of this study was to determine the role of hypolipidemic treatment in the prevention of second primary cancer in colorectal cancer (CRC) survivors. We conducted a retrospective single-institution study of 1401 patients with newly diagnosed colorectal cancer from January 2003 to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 75 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…19), short-term users (RR: 1.10, 95% CI 0.93-1.31), or long-term users (RR: 0.98, 95% CI 0.81-1.20), and these were reported to be not statistically significant (p-values not reported). The increased risk reported in the study by Farwell et al [37] was not statistically significant (univariate HR: 0.94, 95% CI 0.80-1.11, multivariate HR: 0.94, 95% CI 0.77-1.13, p-trend = 0.25), and in the study by Halámková et al [42], although the percentage of patients with UBC was higher on the user group (3.6% vs. 11.3%, or 11/304 vs. 6/53, p = 0.015, compared to a population reference of 2.9%), important factors such as smoking and obesity were not addressed.…”
Section: Studymentioning
confidence: 75%
See 3 more Smart Citations
“…19), short-term users (RR: 1.10, 95% CI 0.93-1.31), or long-term users (RR: 0.98, 95% CI 0.81-1.20), and these were reported to be not statistically significant (p-values not reported). The increased risk reported in the study by Farwell et al [37] was not statistically significant (univariate HR: 0.94, 95% CI 0.80-1.11, multivariate HR: 0.94, 95% CI 0.77-1.13, p-trend = 0.25), and in the study by Halámková et al [42], although the percentage of patients with UBC was higher on the user group (3.6% vs. 11.3%, or 11/304 vs. 6/53, p = 0.015, compared to a population reference of 2.9%), important factors such as smoking and obesity were not addressed.…”
Section: Studymentioning
confidence: 75%
“…Regarding the UBC risk on statin patients, we performed a meta-analysis of four RCTs [27][28][29][30] and six cohort [36,37,[39][40][41][42] studies (Supplementary Table S3). The included population consisted of 13,932 statin users and 13,917 controls for the RCTs analysis, and 544,862 users and 621,806 controls for the cohort studies.…”
Section: Results From the Quantitative Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review of the role of hypolipidaemic treatment in the prevention of second primary cancers in colorectal cancer survivors showed that fibrates did not have a significant chemoprotective effect against cancer. However, the authors note that the subgroup of patients treated with fibrates in their study was too small [23].…”
Section: Introductionmentioning
confidence: 89%